Observation of a tight junction structure generated in LbL‐3D skin reconstructed by layer‐by‐layer cell coating technique. (8th June 2021) - Murakami, Masato; Akagi, Takami; Sasano, Yumi; Chiba, Tomohiro; Narita, Hirokazu; Shimoda, Hiroshi; Akashi, Mitsuru
Abstract: Tissue‐engineered skin equivalents are reconstructed the functions of human skin and can be used as an alternative to animal experiments in basic study or as cultured skin for regenerative medicine. Recent studies confirmed that epidermal tight junctions (TJs), which are complex intercellular junctions formed in the stratum granulosum of human skin, play an important part in the formation of the skin barrier function. In well‐formed reconstructed human skin models, there are several reports on the expression of TJ proteins and their localization in epidermal layer, however, the morphological features of TJ, showing tight junctional contacts and the process of TJ formation have yet to be investigated. In this study, we systematically examined and identified TJ‐related proteins and TJ structure in three‐dimensional (3D) human skin equivalents reconstructed by layer‐by‐layer (LbL) cell coating technique (LbL‐3D Skin). We demonstrate localization of TJ‐related proteins and time course of formation of TJ structure with typical junctional morphology in LbL‐3D Skin. These data provide evidence that the LbL‐3D Skin is an in vitro model with structure and function extremely similar to living skin.